Extended Unemployment in the Congo: A Comparative Analysis by Gender - Zitamelet Kizot Rodolphe Edgard (International Journal of Business and Social Science Research, 2026)
Widespread unemployment in the Congo is massive and multidimensional. It reveals a significant vulnerability in the labor market, with notable differences in unemployment rates between men (66%) and women (62%): men are more affected in terms of formal unemployment and underemployment, while women are more excluded by inactivity, which moderates their unemployment rate but reflects another form of economic fragility. A comparative analysis by sex thus reveals two different forms of vulnerability, which require tailored and complementary policies to reduce precariousness and promote greater participation in the labor market. The article concludes by emphasizing the need for a gender-differentiated approach: for men, it is important to strengthen retraining and entrepreneurship programs; and for women, to develop inclusion policies (childcare, flexible working hours, anti-discrimination measures) to encourage their active participation in the labor market.